E6 The correlation between eye movements and balance in a group of persons with huntington's disease. (13th September 2016) - Ekwall, Camilla; Karlsson, Maria; Sandell, Moa; Hellström, Karin
Abstract : Background: Huntington's disease (HD) is an autosomal dominant degenerative disease where individuals have an increased number of CAG repeats (a genetic abnormality). Two motor symptoms of the disease are reduced: eye movement and postural control. The eye movements affect the postural control, because of that studies concerning these symptoms could contribute to improve the physiotherapeutical interventions for individuals with HD, for example to reduce the risk of falls and improve gait ability. Aims: Analysis of eye movement and postural control data, and their relation, in a group of individuals with HD. Method: The study was retrospective and had a descriptive and correlating design. Forty participants were recruited from the clinical Huntington's team at the University Hospital of Uppsala. The calculations were made from already collected data from the Unified Huntington's Disease Rating Scale (UHDRS) Motor Assessment. Results: The average scores of the eye movements and the postural control items were 0 (normal) and 1 (light effects) respectively, and there was a significant moderate correlation (p = 0.57–0.69) between these variables, in all correlations except one (p = 0.49). Conclusion: There was a moderate correlation between the eye movements and the postural control. The results cannot be generalised for other than the studied population. More studies, on larger patient groups, examining eye movements and the postural control for individuals with HD could lay the foundations for developing physiotherapeutic interventions.